DISTRIBUTION, HABITAT USE, AND LIMITING FACTORS OF GOULD'S TURKEY IN CHIHUAHUA, MEXICO - Alberto Lafon; Sanford D. Schemnitz (Wildlife Society Bulletin)
Abstract: Detailed studies of the Gould's turkey (Meleagris gallopavo mexicana) in its original range in Mexico are lacking. Currently we are investigating the distribution, habitat use, diet, biology, and limiting factors of Gould's turkey in the state of Chihuahua, Mexico. Turkey distribution reports were collected from Forest Management Unit personnel, hunting club members, outfitters, cattlemen, and researchers. Gould's turkeys were found in all the forest units in western Chihuahua. Habitat used by this subspecies is characterized as evergreen woodland and forest communities. Part of the land is used for agriculture, which has adversely impacted a large segment of the subspecies' historical range. In order to assess habitat use, 25 wild turkeys were radio‐equipped and followed since March 1994. Measurements and weights from trapped and hunter‐shot birds were taken. Adult gobblers' average weight (8.5 ± 2.3 kg [SD], 18.7 lbs, n = 34) was 2.2 kg (4.8 lbs) more than hens' (n = 16). Mean male beard length (x = 25.17 cm) was longer than that of most other subspecies. Preliminary data suggested that oak‐pine forest areas were preferred. Home ranges varied from 230 to 4,940 ha. Roost sites averaged 5.4 trees (range 1‐28) and were characterized by ponderosa pine (P. ponderosa), Emory oak (Q. emoryi), and Apache pine (P. engelmannii). Manzanita (Arctostaphylos pungens), fragrant sumac (Rhus trilobata), alligator juniper (Juniperus deppeana), and Panicum seeds were the major plant foods found in the diet, and Lepidoptera and Coleoptera were the main animal components. Average clutch size for 5 nests was 9.4 eggs (range 4‐14). Renesting and subadult female nesting were verified. In general, the suspected limiting factors affecting the population were poaching, lack of conservation education programs, hybridization of wild and domestic turkeys, loss of habitat from wildfires and excessive timber harvest, and human pressure from agriculture and ranching.